Suriye göç edebiyatında ağıt - Alioğlu, Ahmed (My University, 2023)
Göç edebiyatı, Suriye ve Lübnan’dan Amerika'ya birçok şairin göçünden sonra oluşmaya başlamış ve Arap şiirinde modern bir şiir fenomeni olarak kabul edilmiştir. Kötü sosyal koşulların neden olduğu bu göç, şairlerin daha önce bilmedikleri yeni bir Arap şiiri türünün yayılmasının başlangıcını oluşturur. Bu akımın öncüleri Kuzey Amerika'da er_Rabıta el_Kalamiyye (kalem Birliği) ve Güney Amerika'da el_Usbe el_Endelusiyye'yi (Endülüs Grubu) kurmuşlardır. O dönemin en önemli şairleri arasında Cübran Halil Cübran, Îliyyâ Ebû Mâdî, Mihâil Nuayme, Nesîb Arîda, İlyâs Ferhât, Şefîk Ma‘lûf ve diğerleri sayılabilir. Bize duygularını aktararak, yeni memleketlerindeki hayat tarzını, ana vatanlarına özlemlerini dile getirdikleri harika edebi eserler bıraktılar. Bu yüzyılın ilk çeyreğinde(2011'den sonra) , yeni bir şiir akımı oluştu ve özellikleri şekillendi. Suriye'deki savaş sırasında birçok Suriyeli yazar ve şairin aileleriyle birlikte birçok komşu ülkeye göç etmesiyle iltica ve göç edilen ülkelerde göç edebiyatı gelişmeye başlamış, buna parallel olarak da telif ve yayıncılık hareketi ortaya çıkmıştır. Bu edebi ürünlenden en büyük pay Türkiye'ye düşmüştür. Suriye göç literatürünün dünyaya yayılmasına katkıda bulunmak için Türkiye'de birçok yeni yayınevi açılmıştır. Bu araştırmanın amacı gurbet memleketlerde ağıt konusunda kaleme alınan şiir örneklerini derlemek ve bu olguyu (göç literatürü) başlangıç, gelişme, sosyal çevre, tarihsel boyut ve siyasi çerçeve açısından, genel anlamda göç literatürü içerisinde ve özel anlamda ağıt konusu etrafında tahlil etmektir. Özellikle şairlerin vatan özlemlerini ağıt şiirleriyle ölümsüzleştirdikleri göç edebiyatını, ortaya çıkış tarihi ve gelişimini tanıtarak teze giriş yapılacak, ardından anne, baba, eş, çocuk ve şehir ağıtlarını da içeren ağıtın amaclarından bahsedilecektir. Bu türde kaleme alınmış yedi kaside edebi açıdan incelenecektir

Emigration literature began to form after the emigration of many poets from Syria and Lebanon to both South and North America and has been accepted as a modern poetic phenomenon in Arabic poetry. This emigration, caused by bad social conditions, is the beginning of inventing a new type of Arabic poetry that the poets did not know before. the pioneers of this movement established associations that linked them to each other in the countries of emigration, where er_Rabıta al_Kalamiye (Pen Union) in North America and el_Usbe el_Endelusiyye (Andalusian Group) in South America were the fruit of this union. Among the most important poets of that period Gubran Khalil Gubran, Eilya Abu Madi, Mikail Naima, Nesib Arida, Elyas Farhat, Shafik Ma'louf, and others , Who left us wonderful literary works in which they expressed their longing for their homeland and the way of life in their new countries, by conveying their feelings and emotions in their poems and literary works so that the reader can get emotionally involved and share their feelings through these literary works. In the second decade of this century(after 2011), a new poetic phenomenon occurred and its features were formed during the war in Syria, where many Syrian writers and poets emigrated to many neighboring countries with their families, and the emigration literature began to develop in countries of asylum and immigration, so the movement of writing, translation and publishing flourished, and Turkey had the largest share of this literary production, where many new publishing houses were opened to contribute to the dissemination of the Syrian emigration literature in Turkey and from there to the whole world. The aim of this research is to study examples of elegiac poetry in different regions of countries of asylum and to analyze this phenomenon (immigration literature) in terms of its origin, development, social environment, historical dimension and political framework, within migration literature in general, and on the subject of elegiac poetry in particular. The thesis will be presented in particular by defining the emigration literature and the history of its origin and development, then moving on to topics of elegiac poetry that include father, mother, father, children, brother, friend, symbols, and homeland. Seven poems of elegiac poetry will be discussed in this research from an intellectual and artistic point of view.
Keywords: ağıt; Ağıtlar; Arab poetry; Arap şiiri; asylum; Dirges; edebiyat; elegiac poetry; Göç; iltica; literature; Mülteciler, Suriyeli; Refugees, Syrian; Suriye migration; Syria